Association of single nucleotide polymorphisms on chromosome 9p21.3 with cardiovascular death in kidney transplant recipients - Melk, Anette; Schildhorn, Carolin; Hömme, Meike; Knoch, Miriam; Schmidt, Bernhard M. W.; Serth, Jürgen; Scherer, Sabine; Döhler, Bernd; Opelz, Gerhard (Transplantation, 2013)
Background - Recipient death is a leading cause for renal allograft loss. Cardiovascular mortality is the most important cause of death among this patient group. Single nucleotide polymorphisms (SNPs) in a noncoding region close to the CDKN2a/b senescence genes have been associated with higher cardiovascular morbidity and mortality in nontransplant populations. - Methods - We selected 2064 renal transplant recipients: 688 with a known cardiovascular cause of death and 1376 matched controls. DNA specimens were genotyped for the three SNPs with known risk allele (rs10757274, rs2383206, and rs10757278) and one SNP without risk allele (rs518394). Genotyping results were analyzed according to the frequency of risk alleles in the two groups. - Results - The risk allele for three SNPs was detected significantly more often in patients with a known cardiovascular cause of death than in matched controls (all P<0.05). Diabetes and time on dialysis were modifiers of this effect with the presence of high-risk alleles having a stronger impact in diabetic patients and those with longer dialysis time. There was no difference between groups for the investigated SNP without risk allele. - Conclusions - Our results support data from large cohort studies in normal nontransplant populations, which suggested a higher risk for cardiovascular events in individuals carrying certain SNPs in senescence-associated genes. Notably, this finding was obtained in a population known to be at increased risk of cardiovascular death.